An adoption study of parental depression as an environmental liability for adolescent depression and childhood disruptive disorders - Tully, Erin C; Iacono, William G; McGue, Matt (The American journal of psychiatry, 2008)
The authors used an adoption study design to investigate environmental influences on risk for psychopathology in adolescents with depressed parents. Participants were 568 adopted adolescents ascertained through large adoption agencies, 416 nonadopted adolescents ascertained through birth records, and their parents. Clinical interviews with parents and adolescents were used to determine lifetime DSM-IV-TR diagnoses of major depressive disorder, oppositional defiant disorder, conduct disorder, attention deficit hyperactivity disorder (ADHD), and substance use disorders in adolescents and major depression in mothers and fathers. Effects of parental depression (either parent with major depression, maternal major depression, and paternal major depression) on adolescent psychopathology were tested in nonadopted and adopted adolescents separately, and interactive effects of parental depression and adoption status were tested. Either parent having major depression and a mother having major depression were associated with a significantly greater risk for major depression and disruptive behavior disorders in both nonadopted and adopted adolescents. Paternal depression did not have a main effect on any psychiatric disorder in adolescents and, with one exception (ADHD in adopted adolescents), did not predict significantly greater likelihoods of disorders in either nonadopted or adopted adolescents. Maternal depression was an environmental liability for lifetime diagnoses of major depression and disruptive disorders in adolescents. Paternal depression was not associated with an increased risk for psychopathology in adolescents.